Subfamilies of Bi-Univalent Functions Defined by Imaginary Error Functions Subordinate to Horadam Polynomials (European Journal of Pure and Applied Mathematics, 2025)
Several different subfamilies of the bi-univalent function family Ω were introduced and studied by numerous researchers using special functions. In the present paper, utilizing the imaginary error function, we introduce and study a new subfamily FΩ(s, r, u, y, t, λ, τ ) of bi-univalent functions in the open unit disk Θ, which are connected to the Horadam polynomials, and determineinitial coefficients in the Maclaurin series of functions in this subfamily. Moreover, we determine the Fekete-Szeg ̈o inequality for functions in this subfamily. The parameters employed in our major results are specialized, and several fresh outcomes are shown to follow.
Keywords: analytic; bi-univalent; fekete-Szegö; horadam; imaginary error function